The Influence of Heat Treatment on the Corrosion Resistance of Weld Deposits on Steel X8CrNi25-21 - Kantoríková, E.; Frátrik, M. (Archives of Foundry Engineering, 2026)
This work focuses on a comprehensive study of the influence of weld overlays on X8CrNi25-21 austenitic stainless steel, a material known for its excellent heat and corrosion resistance. The main objective is to investigate the mechanisms of sensitization induction in the material due to the thermal cycles associated with the overlay process. Subsequently, the study analyzes the possibility of reversing this undesirable condition through controlled heat treatment. The experimental part includes a detailed characterization of the material before and after welding, as well as after the application of reverse heat treatment. Key parameters evaluated include material hardness and microstructural changes. It is hypothesized that applying a specifically designed heat treatment regimen will allow for the dissolution of precipitated chromium carbides (primarily Cr23C6) at grain boundaries, thereby restoring the local chromium concentration and improving corrosion resistance. The service life of a material plays a very important role in practice, mainly from an economic and, in this case, safety perspective. The aim of this work was to analyze the effect of 70% atmospheric humidity on X8CrNi25-21 steel welds, which are used in roof constructions. The aim of the work was to analyze the effect of heat treatment on intergranular corrosion in steel welds X8CrNi25-21, which is used as a roof structure.